Regulation of ventilatory sensitivity and carotid body proliferation in hypoxia by the PHD2/HIF‐2 pathway. (6th October 2015) - Hodson, Emma J.; Nicholls, Lynn G.; Turner, Philip J.; Llyr, Ronan; Fielding, James W.; Douglas, Gillian; Ratnayaka, Indrika; Robbins, Peter A.; Pugh, Christopher W.; Buckler, Keith J.; Ratcliffe, Peter J.; Bishop, Tammie
Abstract : Key points: Sustained hypoxic exposure increases ventilatory sensitivity to hypoxia as part of physiological acclimatisation. Oxygen‐sensitive signals are transduced in animal cells by post‐translational hydroxylation of transcription factors termed hypoxia‐inducible factors (HIFs). Mice heterozygous for the principal 'oxygen‐sensing' HIF hydroxylase PHD2 (prolyl hydroxylase domain 2) show enhanced ventilatory sensitivity to hypoxia. To analyse the underlying mechanisms, functional (hypoxic ventilatory responses, HVRs) and anatomical (cellular proliferation within carotid bodies) responses were studied in genetic models of inducible and constitutive inactivation of PHD2 and its principal hydroxylation substrates, HIF‐1α and HIF‐2α. Inducible PHD2 inactivation enhanced HVR, similar to constitutive inactivation; both responses were almost entirely compensated for by specific inactivation of HIF‐2α. Inducible inactivation of HIF‐2α, but not HIF‐1α, strikingly reduced ventilatory acclimatisation to hypoxia and associated carotid body cell proliferation. These findings demonstrate a key role for PHD2 and HIF‐2α in ventilatory control and carotid body biology. Abstract: Ventilatory sensitivity to hypoxia increases in response to continued hypoxic exposure as part of acute acclimatisation. Although this process is incompletely understood, insights have been gained through studies of the hypoxia‐inducible factor (HIF) hydroxylase system. Genetic studies implicate these pathways widely in the integrated physiology of hypoxia, through effects on developmental or adaptive processes. In keeping with this, mice that are heterozygous for the principal HIF prolyl hydroxylase, PHD2, show enhanced ventilatory sensitivity to hypoxia and carotid body hyperplasia. Here we have sought to understand this process better through comparative analysis of inducible and constitutive inactivation of PHD2 and its principal targets HIF‐1α and HIF‐2α. We demonstrate that general inducible inactivation of PHD2 in tamoxifen‐treated Phd2 f/f ;Rosa26 +/CreERT2 mice, like constitutive, heterozygous PHD2 deficiency, enhances hypoxic ventilatory responses (HVRs: 7.2 ± 0.6 vs . 4.4 ± 0.4 ml min −1 g −1 in controls, P < 0.01). The ventilatory phenotypes associated with both inducible and constitutive inactivation of PHD2 were strongly compensated for by concomitant inactivation of HIF‐2α, but not HIF‐1α. Furthermore, inducible inactivation of HIF‐2α strikingly impaired ventilatory acclimatisation to chronic hypoxia (HVRs: 4.1 ± 0.5 vs . 8.6 ± 0.5 ml min −1 g −1 in controls, P < 0.0001), as well as carotid body cell proliferation (400 ± 81 vs . 2630 ± 390 bromodeoxyuridine‐positive cells mm −2 in controls, P < 0.0001). The findings demonstrate the importance of the PHD2/HIF‐2α enzyme–substrate couple in modulating ventilatory sensitivity to hypoxia. Key points: Sustained hypoxic exposure increases ventilatory sensitivity to hypoxia as part of physiological acclimatisation. Oxygen‐sensitive signals are transduced in animal cells by post‐translational hydroxylation of transcription factors termed hypoxia‐inducible factors (HIFs). Mice heterozygous for the principal 'oxygen‐sensing' HIF hydroxylase PHD2 (prolyl hydroxylase domain 2) show enhanced ventilatory sensitivity to hypoxia. To analyse the underlying mechanisms, functional (hypoxic ventilatory responses, HVRs) and anatomical (cellular proliferation within carotid bodies) responses were studied in genetic models of inducible and constitutive inactivation of PHD2 and its principal hydroxylation substrates, HIF‐1α and HIF‐2α. Inducible PHD2 inactivation enhanced HVR, similar to constitutive inactivation; both responses were almost entirely compensated for by specific inactivation of HIF‐2α. Inducible inactivation of HIF‐2α, but not HIF‐1α, strikingly reduced ventilatory acclimatisation to hypoxia and associated carotid body cell proliferation. These findings demonstrate a key role for PHD2 and HIF‐2α in ventilatory control and carotid body biology.